PERBANDINGAN PELAKSANAAN LAYANAN ASPIRASI DAN PENGADUAN ONLINE RAKYAT (LAPOR!) PEMERINTAH KOTA BANJARMASIN DENGAN KABUPATEN BANJAR - Siti Soleha; Tomi Oktavianor (Universitas Lambung Mangkurat, 2019)
In this study, the study observed was Comparison of the Implementation of Online People's Aspirations and Complaints Services (LAPOR!) In Banjarmasin City and Banjar District Governments. The Online People's Aspirations and Complaints Service (LAPOR!) Is a social media-based aspiration and complaint facility that is carried out with the principle of easy, integrated, and complete. E-Governments as an effort to use information and communication technology to improve the efficiency and effectiveness, transparency and accountability of the government in providing better public services. LAPOR! implementation! In Banjarmasin City and Banjar Regency, each region has fulfilled the elements of successful implementation of electronic government, namely Support, Capacity and Value. However, the Banjarmasin City Government is more optimal in its implementation because the Banjarmasin City Government is strengthened in its part of the support, namely by conducting more intensive socialization in socializing LAPOR! to the community so that many people know and take part in supporting the successful implementation of LAPOR! in addition to that, the capacity of the Banjarmasin financial section has also compiled the RKA so that every activity carried out can run smoothly because there is clear and detailed planning. In addition, there are several indicators of success such as commitment from the leadership, activeness in disseminating the LAPOR! Application, follow-up on complaints, and good coordination and cooperation with the management team. Whereas the Banjar district government was still not maximized in its socialization activities because there was no direct socialization conducted with the community. And in Banjar District there is no compilation of Budget Details so that the budget is still very limited and becomes an obstacle for carrying out activities.